## Active forum topics

- Eliminate the Arbitrary Constants
- Law of cosines
- Maxima and minima (trapezoidal gutter)
- Special products and factoring
- Integration of 4x^2/csc^3x√sinxcosx dx
- application of minima and maxima
- Sight Distance of Vertical Parabolic Curve
- Application of Differential Equation: Newton's Law of Cooling
- Minima maxima: a²y = x⁴
- Trim and stability

## New forum topics

- Integration of 4x^2/csc^3x√sinxcosx dx
- Maxima and minima (trapezoidal gutter)
- Special products and factoring
- Newton's Law of Cooling
- Law of cosines
- Can you help me po to solve this?
- Eliminate the Arbitrary Constants
- Required diameter of solid shaft
- Differentiate trigonometric function
- Integration $\displaystyle \int \sec 2x ~ dx$

## Recent comments

- Mali po ang equation mo…2 days 6 hours ago
- $x$ is the location where…2 days 17 hours ago
- In double integration method…1 week ago
- Maayo, salamat sa imong…2 weeks 2 days ago
- 24 ft during the 10th second…2 weeks 2 days ago
- The differentiation you need…2 weeks 3 days ago
- Obtain the differential…2 weeks 3 days ago
- Thank you for sharing your…2 weeks 3 days ago
- Based on the differentiation…1 week ago
- Given that $x + y + xy = 1$,…1 week ago

## Create a circle of radius 1

Create a circle of radius 1 with center at (2, 1). The equation of the circle would be (x - 2)

^{2}+ (y - 1)^{2}= 1. Then draw a line through (7, -4) that is tangent to your circle, you can see that you can draw two such lines, one is above the (2, 1) and the other is below the point (2, 1). You only need to draw one of the lines. Call the point of tangency as (x_{1}, y_{1}) and our task now is to locate this point of tangency. You can find (x_{1}, y_{1}) knowing that this point is common to the circle and the line. Once you get (x_{1}, y_{1}), you have now two points on the line to be used to find its equation.## Here is the details of the

Here is the details of the solution:

$(x - 2)^2 + (y - 1)^2 = 1^2$

$(x^2 - 4x + 4) + (y^2 - 2y + 1) = 1$

$x^2 + y^2 - 4x - 2y + 4 = 0$

The circle above will pass through (x

_{1}, y_{1})${x_1}^2 + {y_1}^2 - 4x_1 - 2y_1 + 4 = 0$ ← Equation (1)

Equation of tangent to x

^{2}+ y^{2}- 4x - 2y + 4 = 0$xx_1 + yy_1 - 4\left( \dfrac{x + x_1}{2} \right) - 2\left( \dfrac{y + y_1}{2} \right) + 4 = 0$

$xx_1 + yy_1 - 2(x + x_1) - (y + y_1) + 4 = 0$

$7x_1 - 4y_1 - 2(7 + x_1) - (-4 + y_1) + 4 = 0$

$7x_1 - 4y_1 - 14 - 2x_1 + 4 - y_1 + 4 = 0$

$5x_1 - 5y_1 - 6 = 0$

$y_1 = x_1 - \frac{6}{5}$ ← Equation (2)

Substitute y

_{1}= x_{1}- 6/5 of Equation (2) to Equation (1)${x_1}^2 + (x_1 - \frac{6}{5})^2 - 4x_1 - 2(x_1 - \frac{6}{5}) + 4 = 0$

${x_1}^2 + ({x_1}^2 - \frac{12}{5}x_1 + \frac{36}{25}) - 4x_1 - 2x_1 + \frac{12}{5} + 4 = 0$

$2{x_1}^2 - \frac{42}{5}x_1 + \frac{196}{25} = 0$

$x_1 = \frac{14}{5} ~ \text{and} ~ \frac{7}{5}$

From Equation (2)

$y_1 = \frac{8}{5} ~ \text{and} ~ \frac{1}{5}$

$m = \dfrac{y_2 - y_1}{x_2 - x_1}$

$y - y_1 = m(x - x_1)$

For line L

_{1}$y - \frac{8}{5} = -\frac{4}{3}(x - \frac{14}{5})$

$15y - 24 = -20(x - \frac{14}{5})$

$15y - 24 = -20x + 56$

$20x + 15y - 80 = 0$

$4x + 3y - 16 = 0$

answerFor line L

_{2}$y - \frac{1}{5} = -\frac{3}{4}(x - \frac{7}{5})$

$20y - 4 = -15(x - \frac{7}{5})$

$20y - 4 = -15x + 21$

$15x + 20y - 25 = 0$

$3x + 4y - 5 = 0$

answer## I am happy to register this.

I am happy to register this.